A broadband GaN HEMT power amplifier based on feeding capacitance compensation method. Issue 3 (14th January 2021) - Zhao, ZiMing; Zhu, Xiao‐Wei; Zhang, Lei
Abstract: In order to better cover the frequency band of fifth‐generation communication system in sub‐6GHz frequency, a feeding capacitance compensation method is proposed to improve the bandwidth and efficiency of power amplifier (PA). By adding different feeding capacitance at the drain supply voltage network, resonance valley points occurred at different frequencies are compensated to achieve wide bandwidth and high‐efficiency. For validation purpose, a PA prototype is designed with using a 10‐W Cree GaN high electron mobility transistor device. Maximum 64.7% efficiency has been measured over 80% bandwidth from 2.2 to 5.1 GHz, with maximum output power of 13.5 W. The measurement revealed an adjacent channel leakage ratio of better than −50.3 dBc after digital pre‐distortion while being driven with a 40‐MHz orthogonal frequency‐division multiplexing modulated signal with a peak‐to‐average power ratio of 6.5 dB at an average output power of 32.5 dBm.